Examining the Narrative Structure and Function of The Story of Tobias and Sarah: A Labovian Approach - Saputra, Yongki; Sulastri, Tetet; Fairuz, Fairuz (ITScience (Information Technology and Science), 2025)
In the study of modern linguistics, narrative theory offers a way to understand how language organizes human experience into meaningful discourse. One of the most influential models is Labov's Natural Narrative Model theory (Labov & Waletzky, 1967), which explains that each narrative consists of six main components that function socially and communicatively. The story of Tobias and Sarah's marriage in the Book of Tobit (Tobit 7–11) is interesting to study because it contains a complete story structure and is full of faith and moral values. This study aims to analyze the structure and narrative function of the story of Tobias and Sarah based on Labov's narrative model, as well as explain how linguistic forms support the delivery of theological messages in texts. This study uses a descriptive-qualitative approach with a narrative analysis method. The data were taken from the text of the Book of Tobit, which is one of the parts of the Deuteronomic Bible, and were analyzed based on the six components of Labov's narrative: abstract, orientation, complicating action, evaluation, resolution, and coda. The analysis shows that the story of Tobias and Sara has a complete narrative structure with two dominant stages, namely, complicating action and resolution. The evaluation stage occupies a central position because it affirms theological meaning through prayer and confession of faith. The application of Labov's theory proves that narrative structure functions not only as an arrangement of events but also as a linguistic medium that expresses the values of faith, morality, and divine inclusion in human life.